“Island-scape”: Investigating the Multilingual Linguistic Landscape of a Philippine Island - Ivan Dolph F. Fabregas (SUVANNABHUMI, 2025)
Many linguistic landscape (LL) studies have been done in the Philippines, but despite its archipelagic nature, there is not much LL research that considers the context of an island. This paper investigates the LL of a Philippine island, with special attention to multilingualism. It focuses on the languages displayed in the signs, top-down and bottom-up signs, their functions, and their materiality. These features are analyzed to describe how the island’s LL establishes orders of indexicality. The results show that despite the local language being used in the daily affairs of the locals, English dominates the island’s LL. Moreover, the LL is dominated by top-down signs, which, considering their materiality, places the local government in a memorializing and authoritative position, leaving the public voice seemingly suppressed. This study coincides with previous research about the omnipresence of the global English and the preference for majority over minority languages, especially in LL.